Understanding Employee Burnout and Its Impact on Knowledge Transfer Effectiveness: Evidence from Service-Based Organizations - Madyastha Aji Bhirawa; Risman Nugraha; Muhammad Nurrifqi Fuadi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Employee burnout has become a critical challenge for service-based organizations, where organizational performance heavily depends on employees’ knowledge, expertise, and collaborative capabilities. This study aims to examine the impact of employee burnout on knowledge transfer effectiveness within service-oriented organizations. Using a conceptual literature-based approach, this research explores how burnout dimensions, including emotional exhaustion, depersonalization, and reduced personal accomplishment, influence employees’ willingness and ability to share knowledge. The analysis is grounded in the Conservation of Resources Theory, Job Demands-Resources Theory, Knowledge-Based View, and Organizational Learning Theory to explain the mechanisms linking psychological resource depletion with disrupted knowledge flows. The findings indicate that burnout negatively affects knowledge transfer effectiveness by reducing employee engagement, weakening interpersonal trust, limiting communication quality, and encouraging knowledge-hiding behaviors. Emotional exhaustion encourages employees to preserve remaining psychological resources, while depersonalization reduces social interactions and collaborative learning opportunities. Consequently, organizations experiencing high levels of burnout may encounter knowledge loss, reduced innovation capacity, and declining service quality. This study highlights the importance of organizational support, employee well-being initiatives, and resource management strategies to mitigate burnout and strengthen sustainable knowledge transfer practices in service-based organizations.